Association of Hyperuricemia With Hypertension In Pakistani Population - Attia Khaliq; Tariq , Abdul Moueed; Karamat ali; Shahzeb Ahmad Satti; Shahzeb Ahmad Rehman; Hafiz Yasir Rehman (Journal of Bahria University Medical and Dental College)
Objective: To find an association between Hyperuricemia and Hypertension in patients presenting in outpatients department for regular check-up. Study design and Setting: Case Control Study design conducted at Pak Emirates Military Hospital Rawalpindi (PEMH), Medical Outpatient department (OPD) from 4th Feb, 2017 to 4th Aug, 2017. Methodology: A total of 200 patients, with 100 cases and 100 controls fulfilling the selection criteria were included in the study, which were selected from Medical OPD of PEMH. An informed written consent was taken. The Demographic such as age, gender were obtained. Veriable upon selection into study group, the blood samples were taken and two groups of patients were made on the basis of normal or raised uric acid levels. The Serum Uric Acid (SUA) was measured in the patients. Then blood pressure was measured by using sphygmomanometer by researchers themselves. If BP level was >140/90mmHg on 2 separate occasions, or patient is already a known case of hypertension, then hypertension was labeled. Results: The mean age (years) in the study was 54.79 + 8.96. There were 136 (68%) male and 64 (32%) female patients. The frequency and percentage of hypertension in cases and control groups was (84%) and (41%) patients respectively which was statistically significant with a p-value of 0.000. The Odds ratio was found to be 7.55. Conclusion: It was concluded that there was an association found between Hyperuricemia and Hypertension.